Breast cancers originating from the terminal ductal lobular units: In situ and invasive acinar adenocarcinoma of the breast, AAB. Issue 152 (July 2022) - Tabár, László; Dean, Peter B.; Tucker, F. Lee; Yen, Amy Ming-Fang; Fann, Jean Ching-Yuan; Lin, Abbie Ting-Yu; Smith, Robert A.; Duffy, Stephen W.; Chen, Tony Hsiu-Hsi
Highlights: The TDLUs are the site of origin of most breast cancers. The mammographic presentation of breast cancer indicates the site of origin. Cancers originating in the TDLUs have four imaging biomarkers. Determination of TDLU origin helps to resolve errors in cancer histopathology terminology. Early detection can control cancers of TDLU origin. The unique large format, 3-D histology images support the validity of imaging biomarkers. Multifocal AAB tumours are as frequent as unifocal AAB tumours and have a poorer prognosis. Abstract: Purpose: To use mammographic tumour features (imaging biomarkers) to identify and investigate breast cancers originating from the terminal ductal lobular units (TDLUs) of the breast in order to overcome the confusion arising from the current histopathology terminology, which calls cancers arising from the TDLUs either "ductal" or "lobular". Method: Prospectively collected data from a randomized controlled mammography screening trial with more than four decades of follow up, and data from the subsequent population-based service screening program in Dalarna County, Sweden, provided the database necessary for studying nonpalpable, primarily screen-detected breast cancer cases in their earliest detectable phases. Large format thick (subgross) and thin section histopathologic images of breast cancers originating from the TDLUs were correlated with their mammographic tumour features (imaging biomarkers) and long-term patient outcome. Results: This systematic correlation indicates that imaging biomarkers can reliably determine the site of origin of breast cancers arising from the terminal ductal lobular units (TDLUs). This breast cancer subgroup has four specific mammographic tumour features: the in situ carcinomas developing from the TDLUs appear as powdery or crushed stone-like calcifications, while the invasive carcinomas appear as stellate/spiculated or circular/oval shaped tumour masses. These features are easily identified with breast imaging, either alone or in combination, unifocal or multifocal. We propose calling breast cancers of TDLU origin acinar adenocarcinoma of the breast (AAB). Conclusions: The era of early detection necessitates rectifying the current, confusing histopathological nomenclature to one that is based on the anatomical site of origin of breast cancers. Invasive cancers originating from the TDLUs are either stellate/spiculated or circular, irrespective of the complex WHO histopathologic terminology. The mortality reduction accomplished by participation in mammography screening is mostly accomplished by identifying and treating the AABs in their non-palpable, early phase. AABs detected when < 15 mm diameter with no associated carcinoma originating from the major lactiferous ducts (ductal adenocarcinoma of the breast, DAB) have a good to excellent long-term outcome, irrespective of the current terminology, which tends to lead to overtreatment of these early invasive tumours. The conventionally used prognostic factors, including immunohistochemical biomarkers, fail to identify those 1–14 mm invasive AABs tumours that are eventually fatal. This identification can be made preoperatively by including the characteristic mammographic tumour features, imaging biomarkers, in primary diagnosis, treatment planning, and predicting long-term patient outcome. Forthcoming articles will address breast malignancies originating from structures of the breast other than the TDLUs.